Mechanisms of Alcohol-Facilitated Intimate Partner Violence. (August 2015) - Eckhardt, Christopher I.; Parrott, Dominic J.; Sprunger, Joel G.
Intimate partner violence (IPV) is a critical public health problem that requires clear and testable etiological models that may translate into effective interventions. While alcohol intoxication and a pattern of heavy alcohol consumption are robust correlates of IPV perpetration, there has been limited research that examines the mediating mechanisms of how alcohol potentiates IPV. We provide a theoretical and methodological framework for researchers to conceptualize how alcohol intoxication causes IPV, and propose innovative laboratory methods that directly test mediational mechanisms. We conclude by discussing how these innovations may lead to the development of interventions to prevent or reduce alcohol-related IPV.